The Influence of Career Development, Work Environment, and Rewards on Employee Performance Mediated By Work Motivation (Empirical Study: Employees at PT Global Loyalty Indonesia) - Hidayat, Riyan; Heryjanto, Andreas (Green Publisher Indonesia, 2024)
The purpose of this study was to determine the effect of Career Development, Work Environment, and Rewards on Employee Performance with Work Motivation as a mediating variable at PT Global Loyalty Indonesia. This study uses a quantitative approach. The survey was conducted on 105 respondents with the criteria that respondents were permanent employees at PT Global Loyalty Indonesia. Data were analyzed using the Structural Equation Model (SEM) and data processing using the Partial Least Square (PLS) approach with the SmartPLS version 3.0 program. The results of the study showed that the variables Career Development, Work Environment, Rewards and Work Motivation have a positive and significant effect on Employee Performance. In addition, Career Development, Work Environment, Rewards also have a positive and significant effect on Work Motivation. The results of indirect testing show that the Work Motivation variable mediates the relationship between Career Development and Employee Performance, then mediates the relationship between Work Environment and Employee Performance, and mediates the relationship between Rewards and Employee Performance. This study provides practical implications for companies to always pay attention to Career Development, Work Environment, and Awards in the company so that employees can work safely and comfortably, so that Employee Performance and Work Motivation can increase.